COVID-19 Pandemic and Reduced Physical Activity: Is There an Impact on Healthy and Asthmatic Children? - Ferrante, Giuliana; Mollicone, Desiree; Cazzato, Salvatore; Lombardi, Enrico; Pifferi, Massimo; Turchetta, Attilio; Tancredi, Giancarlo; La Grutta, Stefania (Frontiers in Pediatrics, 2021)
Physical activity (PA) has been seen to improve asthma symptoms, lung function, and quality of life, as well as to reduce airway inflammation and bronchial responsiveness. As a consequence of the COVID-19 pandemic, the minimal amount of PA recommended by the World Health Organization—i.e., about 60 min/day of moderate-to-high intensity—is difficult to achieve for many children, particularly those living in urban areas. Short-term changes in PA because of the COVID-19 pandemic may become habitual, increasing the risk of adverse asthma outcomes in children. Indeed, prolonged home confinement during the COVID-19 pandemic reduces PA levels and increases sedentary behaviors, possibly impairing immune system function and increasing susceptibility to inflammatory diseases. However, there is limited evidence regarding the effects of lockdown due to COVID-19 on PA and sedentary behaviors in asthmatic children. Given that children stay longer indoors, indoor air pollution represents a major issue to consider during home confinement. This narrative review aims to summarize the available evidence about the impact of decreased PA and increased sedentary behaviors on children with asthma during the COVID-19 pandemic. In addition, strategies for supporting PA in children with asthma during the COVID-19 pandemic are suggested, also looking at the issue of indoor air quality.